OPTIMIZATION OF CULTURE CONDITIONS FOR A BIOFILM FORMING BACTERIUM - MD. TOWHID HOSSAIN; MD. KAMAL UDDIN (International Journal of Pharma and Bio Sciences, 2014)
Oral hygiene is an essential component of human health. Dental caries is one of the most common diseases of man. Some specific species of bacteria are responsible for the formation of this disease. In the present investigation, biofilm forming organisms were isolated from dental caries affected man. The isolates were screened using test tube assay, glass cover slip assay and microtiter plate assay. Different conditions for better biofilm formation and antibiotic susceptibility of the selected organism were investigated. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) was also determined. Among the selected isolates, Streptococcus mutans was found as better biofilm former that was finally selected for detailed study. Optimized culture conditions for biofilm formation were found 37ºC for 24 hrs of incubation with the medium pH 6.5 by the selected isolate. Glucose and yeast extract induced biofilm formation. It was found that the selected isolate was sensitive to ciprofloxacin and tetracycline; intermediate to chloramphenicol and gentamicin; and resistant to amoxicillin, ampicillin, penicillin, cefixime and erythromycin. Results of this study suggest reducing excessive consumption of sugary foods and drinks to prevent the occurrence of dental caries. In case of therapeutic use, antibiotics should be given depending on the basis of antibiotic susceptibility.